Orientasi Pengaturan Organisasi Serikat Buruh atau Serikat Pekerja Dalam Konteks Hukum Nasional - Suhartoyo Suhartoyo (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract The research aims to determine the organization of labor organizations in the context of national law in Indonesia. The results of the study show that trade union organizations that can represent workers/laborers in dispute in the Industrial Relations Court are trade unions that have fulfilled the requirements for the formation of trade unions and who have made notice and record to the labor agency, this provision is technically clarified in Decree of the Minister of Manpower and Transmigration No. 16 of 2001 Article 2 to Article 10 which provides an explanation of two basic things, namely: Written notification to the local manpower agency if a trade union / labor union has been formed Written notification to its partners (in accordance with its level) after receiving number of registration evidence, written notification to the new local manpower agency in accordance with the transfer of domicile of the trade union / labor union, written notification to the labor agency that provides the number of registration evidence if there is a change in the Articles of Association / By-Laws, Written notification to local labor agencies for trade unions/labor unions that receive financial assistance from overseas for organizational activities, Written notification to local labor agencies for trade unions/labor unions that have been disbanded to revoke registration records . Keywords: Labor organizations, Employment, National Law Abstrak Penelitian bertujuan untuk mengetahui pengaturan organisasi buruh dalam konteks hukum nasional di Indonesia. Hasil penelitian menujukan bahwa Organisasi serikat pekerja/buruh yang dapat mewakili pekerja/buruh yang bersengketa di Pengadilan Hubungan Industrial adalah serikat pekerja/buruh yang telah memenuhi syarat pembentukan serikat pekerja/buruh dan yang telah melakukan pemberitahuan dan pencatatan kepada instansi ketenagakerjaan, ketentuan ini secara teknis diperjelas dalam Keputusan Menteri Tenaga Kerja Dan Transmigrasi No 16 Tahun 2001 Pasal 2 hingga Pasal 10 yang memberikan penjelasan dua hal mendasar yakni: Pemberitahuan tertulis kepada instansi ketenagakerjaan setempat bila serikat pekerja/serikat buruh telah terbentuk Pemberitahuan tertulis kepada mitra kerjanya (sesuai tingkatannya) setelah mendapat nomor bukti pencatatan, Pemberitahuan tertulis kepada instansi ketenagakerjaan setempat yang baru sesuai melakukan perpindahan domisili serikat pekerja/serikat buruh, Pemberitahuan tertulis kepada instansi ketenagakerjaan yang memberikan nomor bukti pencatatan bila terjadi perubahan anggaran dasar/anggaran rumah tangga, Pemberitahuan tertulis kepadan instansi ketenagakerjaan setempat bagi serikat pekerja/serikat buruh yang menerima bantuan keuangan dari luar negeri untuk kegiatan organisasi, Pemberitahuan tertulis kepada instansi ketenagakerjaan setempat bagi serikat pekerja/serikat buruh yang telah bubar untuk dicabut tanda bukti pencatatan. Kata Kunci: Organisasi buruh, Ketengakerjaan, Hukum Nasional